ANALISIS KINERJA NASABAH PT. BANK “AA” Tbk. DENGAN MENGGUNAKAN ECONOMIC VALUE ADDED (EVA) ANALISIS Z SCORE ALTMAN DAN NILAI SAHAM - Anik Sri Rahayu; Dwidjono Hadi Darwanto (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2006)
This research aim to know growth of performance of is effort and client share performance of Middle Business customers PT.Bank “AA” Tbk which have go public with analysis EVA (Economic Value Added), Z Score of Altman and Intrinsic Vlaue of Share. The Analysis expected can be enchanced in package analysis credit of new application, lengthening and also addition (supplies) of credit, so that channeling of credit can give security guarantee to banking.Research conducted by calculating and analyzing value of EVA, Z Score and Intrinsic Value of compared to share (is) Vlaue Stocks Market from 13 (thirteen) Middle Business customers of PT. Bank “AA” Tbk which have go public and hereinafter lok for correlation EVA with Z Score, EVA with Value Stocks Market and Z Score with Value Stocks Market. Result of calculation indicate that :Acquirement of net profit do not is forever followed with result of assessment of EVA which are positive, and even negativity, its meaning of acquirement of net profit cannot cover of is expense of invested capital, so that company monetarily unable to create value (create value) to stakeholder.Customers majority of PT.Bank “AA” Tbk which have go public though can obtain get net profit, but assess its Z Score lower that is d” 1,81 or reside in at high monetary difficult area and flange can to bankruptcy.Majority assess customers stocks market PT.Bank “AA” Tbk which have go public reside in under intrinsic value of value him in fact. This condition can be interpreted that stocks market value do not express the condition of its company’s finance.Correlation between examine variables in this article that is between value of EVA with Z Score, Value of EVA with Value Stocks Market and Z Score with each Value Stocks Market show correlation in existence. Though there no its correlation, analysis of EVA, Z Score and Intrinsic Value of Share require to be enhanced in package analyze credit PT.Bank “AA” Tbk to be monitoring of condition finance of customers more intensive.